Noncovalent interactions in hydrogenation and hydroformylation - Koshti, Vijay S.; Chikkali, Samir H. (Noncovalent Interactions in Catalysis, 2019)
This chapter summarizes the fundamentals of hydrogenation and hydroformylation reactions. An overview of state-of-the-art developments is presented to set the context. Subsequently, the significance of noncovalent interactions in these reactions is discussed in detail. Hydrogen bonding has been one of the leading noncovalent interactions that has been very frequently used in catalysis, including hydrogenation and hydroformylation reactions. Recent examples from the literature are presented to illustrate the role of hydrogen bonding in hydrogenation and hydroformylation. The impact of hydrogen bonding on catalyst development through self-assembly and the role of hydrogen bonding in directing a substrate to achieve high enantiomeric excess are discussed.